Putting Labour Law to Work: Imperative of Race Conscious Labour Law - Arumugam, Harshini (Dalhousie Law Journal, 2026)
History shows that race and labour are deeply connected in Canada. For the labour movement to advance racial equality, it must contend with this reality. Through a critical race analysis, this paper examines how race-evasive approaches in labour laws and practices have contributed to systemic racial inequality. It argues that race-conscious strategies are essential for addressing the specific experiences and needs of racialized workers. By leveraging existing legal tools and intentionally incorporating race-conscious approaches into areas such as collective bargaining, the collective agreement, and the duty of fair representation, labour law can be a powerful mechanism for achieving racial justice in the workplace.

Unjust Transition: The Future of Fossil Fuel Workers - Bettini, Anna (Labour / Le Travail, 2026)
This article reviews the book, "Unjust Transition: The Future of Fossil Fuel Workers," edited by Emily Eaton, Andrew Stevens, and Sean Tucker.

Salud y Shalom: Conversations with Jewish Veterans of the Abraham Lincoln Brigade - Bick, Sam (Labour / Le Travail, 2026)
This article reviews the book, "Salud y Shalom: Conversations with Jewish Veterans of the Abraham Lincoln Brigade," by Joseph Butwin.

Social Support, Strain, and Surveillance: Peer Relationships and Representation among Migrant Farm Workers in Canada - Borrelli, Erika (Labour / Le Travail, 2026)
Workplace representation – the process through which workers voice concerns, negotiate conditions, and participate in decision-making – can be a crucial mechanism for reducing employment strain. Access to such structures is particularly vital for precarious workers, like temporary migrant farm workers in Canada, who face intensified demands owing to employer-tied contracts, congregate living arrangements, and persistent fears of job loss and deportation. Drawing on qualitative interviews and focus groups with migrant farm workers in three agriculturally dense regions in southern Ontario, this study explores the workers’ perceptions of one form of workplace representation: peer representation. While peer representation may foster lateral communication and social support for an otherwise isolated workforce, it is complicated by the structural precarity that intensifies competition and conflict among migrant farm workers. This article demonstrates how the conditions of entry and residency for migrant farm workers in Canada generate lateral surveillance and intra-worker control, amplifying workplace pressures and demands and reinforcing the strain that peer representation might otherwise help to alleviate.
Keywords: employment strain; lateral surveillance; migrant farm workers; precarious employment; workplace representation

The Evolution of Broad-Based Employee Ownership in Canada - Busaan, Lorin; Pek, Simon (International Review of Applied Economics, 2026)
Inspired by the recent national policy framework establishing the Canadian Employee Ownership Trust, we survey the landscape of broad-based employee ownership (BBEO) in Canada, focusing on the two prominent forms: worker co-operatives and broad-based employee share ownership. We conceptualize BBEO based on two inclusion criteria: the percentage of shares held by employees and the breadth of access to ownership opportunities. We also draw attention to two other relevant factors: the extent of employee control rights and degree of equality of share allocation. We then discuss the evolution and prevalence of the two forms of BBEO in Canada, utilizing limited available data and supplementing with illustrative examples. Finally, we call for an integrated and comparative research and policy agenda that bridges worker co-operatives and broad-based employee share ownership models.
Keywords: Canadian Employee Ownership Trust; J54; J58; P13; Worker co-operative; broad-based employee ownership

Ships of State: Literature and the Seaman’s Labour in Proto-Imperial Britain - Cadigan, Sean T. (Labour / Le Travail, 2026)
This article reviews the book, "Ships of State: Literature and the Seaman’s Labour in Proto-Imperial Britain," by Laurie Ellinghausen.

Uneven Development in the Platform Economy: Stratified Immigration Policies and Uneven Access to Transnational Social Protections in North America - Cervantes-Macías, María E. (Digital Geography and Society, 2026)
How do digital platforms, such as Uber, Amazon, or DoorDash, reterritorialize social protections for immigrant workers at urban, national, and transnational scales? In this paper I show how they function as tools of economic integration, situating interplays between states, markets to generate new territorial configurations and exclusions in the digital economy. By analyzing the role of immigrant workers in the platform economy, I aim to show how platform economies both enable and constrain transnational mobility, deepening global inequalities through the uneven impact of flexible labour mediated by digital infrastructures. I focus specifically on software engineers and gig workers, who perform what Vallas and Schor (2020) identify as “geographically tethered work”. These two migrant groups allow me to observe how platformization has reterritorialized labour relations. Providing an analysis of different immigrant workers in the North American platform economy, I aim to show the ways in which immigration status makes these labour relations more precarious, increasing the reliance on transnational infrastructures of care.
Keywords: Credentialized mobility; Gig workers; Immigrant labour; Platform economy; Reterritorialization; Social protections; Uneven development

Migrant Workers and the Ambiguities of Digitally Mediated Work in Canada - Cervantes-Macías, María; Huot, Suzanne (Global Networks, 2026)
Digitally mediated work is often framed as an opportunity for migrants to have greater flexibility, mobility and transnational connectivity. However, less attention has been paid to how digitally mediated work intersects with immigration systems that regulate settlement, labour market incorporation and belonging. Drawing on qualitative interviews with 50 migrant workers engaged in gig and remote work in Canada, this article examines how digitally mediated labour complicates migrants’ experiences of integration within Canada's multi-step immigration regime. Engaging literature on digital work, migrant incorporation and liminality, the article conceptualizes ambiguity as a condition emerging at the intersection of digitally mediated employment and temporally conditional migration pathways. Although digitally mediated work does facilitate transnational connections and flexible forms of employment, it also weakens access to workplace sociality, professional networks, and forms of ‘Canadian experience’ often associated with long-term integration and permanent residence pathways. The findings show how migrants experience overlapping spatial, affective and temporal ambiguities as they navigate remote and gig work alongside uncertain immigration trajectories. By examining how digitally mediated work reshapes processes of settlement and belonging, this article contributes to debates on migration, digital economy and the changing relationship between work, mobility and incorporation in contemporary immigration regimes.
Keywords: Canada; digitally mediated work; gig work; liminality; migrant workers; remote work

The Persistent Roots of Racial Capitalism in the Era of Digital Platforms - Chatterjee, Anuneeta (Labour / Le Travail, 2026)
This essay examines the expansion of digital platforms through the lens of racial capitalism, focusing on their implications for people of colour in the Global South and migrant populations. It begins by outlining racial capitalism as a theoretical framework that extends beyond classical Marxism by centring the historical and ongoing racialization of labour, dispossession, and accumulation. Drawing on foundational insights from W. E. B. Du Bois and Cedric Robinson, the essay situates capitalism as inherently structured by racial hierarchies rather than merely class relations. It then engages in a critical review of recent scholarship addressing racial capitalism across domains such as social reproduction, migration, and border regimes, highlighting how digital platforms intensify and reorganize these dynamics. The analysis emphasizes how digital infrastructures reproduce longstanding patterns of exploitation, surveillance, and differential mobility while rendering racialized bodies central to global circuits of labour and value extraction. Finally, the essay applies this framework to the study of digital migration and embodiment, illustrating how platform-mediated environments both constrain and reshape the lived experiences of racialized populations. By foregrounding the interplay between race, technology, and political economy, the essay argues for the continued relevance of racial capitalism in understanding contemporary forms of inequality and in envisioning alternatives.

"I Have a Lot Working Against Me": Trans Precarious Labourers in Canada - Chudyk, Elliot; Devor, Aaron; Lepp, Annalee (Bulletin of Applied Transgender Studies, 2026)
While we know that transgender people are not a monolith, the spectrum of labour precarity that exists for trans workers as well as the additional factors that lead some trans people into deeper levels of life precariousness remain understudied. In this article, we consider how employment precarity impacts trans peoples' quality of life, and how trans peoples' social and material conditions mediate their overall life precarity alongside their experiences of labour precarity. This article is based on 55 in-depth, semi-structured interviews, including 41 interviews with trans precarious workers and 14 with service providers who have worked with trans people experiencing precarious labour. Our analysis highlights participants embodied experiences of labour precarity and explores how varied positions of marginality and material barriers among trans people mediate the kinds of precarity they face. Examining participants' recollections and personal narrations, we explored relationships among poverty, disability, migration, gender, and labour precarity as well as trans workers' deployments of hope, agency, and resistance.

Spatial Control, Precarity, and Union Resistance in Digital Remote Work: An Analysis of ‘Work From Home’ in US and Canadian Call Centres - Doellgast, Virginia; O’Brady, Sean; Kim, Jeonghun (Work, Employment and Society, 2026)
This article analyses the experiences of US and Canadian call centre workers and their unions with the shift from physical call centres to ‘work from home’ (WFH) arrangements. Drawing on interviews, focus groups and a worker survey, the authors find that the shift enabled new forms of spatial control grounded in worker preferences for remote work and associated with different forms of precarity. Management control over the physical location of work could increase job insecurity; control over the costs and risk associated with WFH arrangements could increase income insecurity; and control over communication between workers and with their unions could increase collective representation and voice insecurity. Local unions engaged in modes of resistance to spatial control, but with uneven success. Findings suggest that labour power requires union strategies that both defend WFH rights and develop protections targeted at forms of precarity associated with being able to work from home.

Statesman of the Piano: Jazz, Race and History in the Life of Lou Hooper - Dumais, Samia (Labour / Le Travail, 2026)
This article reviews the book, "Statesman of the Piano: Jazz, Race and History in the Life of Lou Hooper," edited by Sean Mills, Eric Fillion and Désirée Rochat.

Union Organizing in the Northern Canadian Mining Industry - Fitzpatrick, Mason; Mills, Suzanne (Labour / Le Travail, 2026)
For much of the 20th century, mining was a highly unionized sector, including in the Canadian North. From the 1960s to the 1990s, there was near-complete union coverage in mines in the northern territories, significantly increasing the share of wealth and political power claimed by many northern mining workers. Today, only two of ten producing mines are unionized: the Ekati diamond mine in the Northwest Territories (Public Service Alliance of Canada [ psac]) and the Mary River mine in Nunavut (International Union of Operating Engineers [ iuoe]). This article explores the reasons for this decline and contemporary barriers to organizing, drawing on archival research, document analysis, and interviews with Indigenous organizations, union organizers, servicing staff, and officials. Changes in labour practices – such as the use of long-distance commuting, subcontracting, impact and benefit agreements ( ibas), and the shift to smaller, more highly skilled workforces – have created a more challenging organizing environment. These external challenges are compounded by internal union issues, including a failure to prioritize northern organizing and to build meaningful relationships with Indigenous communities and governments. We draw on these results to suggest strategies for overcoming these barriers. These included targeting workers in the remediation phase mines and catering and housekeeping workers to gain a foothold in the sector, locating choke points in the fly-in/fly-out production process, investing in offices and permanent organizing staff in northern cities, and working to decolonize unions through education and meaningful relationships with Indigenous communities.

Deskilled and Degraded: The Interaction of Precarious Status and Precarious Employment Trajectories for Migrant Workers in Canada - Foster, Jason; Coderre, Mylène; Carranza-Hernandez, Giovanni; Mahmood, Zainab (Labour / Le Travail, 2026)
This research explores the intersection of precarious legal status and precarious employment of migrants who came to Canada with a temporary status, whether for work, study, or protection purposes. Drawing on data collected from 148 interviews with precarious-status migrants, the article investigates how transitions in status impact employment trajectories. It builds upon a mixed-method analysis, identifying how employment precarity intensifies with increased status insecurity, which results in progressive deskilling and the degradation of working conditions over time. By foregrounding deskilling as a cumulative and temporal process, this study demonstrates how Canada’s temporary migration regime systematically deteriorates migrant workers’ skills and opportunities, extending precarity beyond the immediate moment of employment. This analysis contributes to an understanding of the lived experiences of migrant workers, highlighting the long-term effects of migration policies and regulations on employment and working conditions.
Keywords: Canada; deskilling; migrant workers; precarious employment; precarious status

Invested in Crisis: Public Sector Pensions Against the Future - Gupta, Priya; Skerrett, Kevin (Labour / Le Travail, 2026)
This article reviews the book, "Invested in Crisis: Public Sector Pensions Against the Future," by Tom Fraser.

From “Offender” to “Employee”: Canadian Prison Labour and Neoliberal Citizenship - Haentjens, Sandrine; Scanlan, Padraic X. (Labour / Le Travail, 2026)
This article analyzes a neoliberal redefinition of citizenship as market participation through the lens of prison labour in Canadian federal penitentiaries. We focus on corcan, a special operating agency of Correctional Service Canada, which employs approximately 4,000 prisoners in various industries. Despite performing tasks like those of free workers, incarcerated individuals are not recognized as employees under Canadian law and are excluded from employment protections. corcan emphasizes employability as a key criterion for evaluating an offender’s rehabilitation. In effect, many prisoners must demonstrate evidence of compliance with a specific model of labour-market participation in order to be paroled, and to be restored to the liberties and rights of citizenship. We highlight the ideological and practical implications of this transformation, suggesting that prison labour serves as both a means of maintaining prison discipline and a window into the logic of a market-driven society. We conclude by exploring the broader significance of these changes for understanding citizenship and labour relations.
Keywords: CORCAN; Correctional Service Canada; citizenship; coerced labour; labour markets; neoliberalism; prison labour; rehabilitation

Law at Work: The Coercion and Co-option of the Working Class - Hammoudi, Ali (Labour / Le Travail, 2026)
This article reviews the book, "Law at Work: The Coercion and Co-option of the Working Class," by Harry Glasbeek.

The Open Shop, Closed Shop, Agency Shop, and Union Default in Comparative Perspective: Members, Resources, and Individual Autonomy - Harcourt, Mark; Gall, Gregor (Industrial Relations Journal, 2026)
Strategies designed to revive the declining union movement require new resources and new members for success. For this, many unions often used closed or agency shops. We compare these with the now dominant open shop as well as the union default. These options are assessed by asking how effective would each be at securing both members and resources for unions; and how much would each option protect and/or advance worker's autonomy in terms of various individual freedoms? Though closed and agency shops have many merits, especially in relation to the open shop, we conclude that the union default is superior to both.
Keywords: closed shop; union default; unions; worker representation

Fit for the Task? Assessing the Suitability of Canadian Labour Law to Respond to New Forms of Technology in the Workplace - Hastie, Bethany; Galway, Devin (UBC Law Review, 2026)
This article takes up the challenge of examining whether, and to what extent, existing labour laws in Canada are equipped to respond to new technological changes in the workplace. While the notion that technology changes labour is not new, both the types of technology associated with this new wave of change, and their rapid deployment, make this an urgently needed inquiry, given their impacts on material working conditions. Further, given that core statutory provisions regulating labour relations in Canada have remained relatively unchanged over the past 50 years, there is reason to speculate about their continued relevance, or suitability to respond to new technology in the workplace. --From Introduction

Shifting Gears: Canadian Autoworkers and the Changing Landscape of Labour Politics - High, Steven (Labour / Le Travail, 2026)
This article reviews the book, "Shifting Gears: Canadian Autoworkers and the Changing Landscape of Labour Politics," by Stephanie Ross and Larry Savage.

Unpaid Work and Feminist Alliances across Difference: Three Local Studies of Wages for Housework Organizing in Canada - Hillyard Little, Margaret; Marks, Lynne; Hughes, Christine; Watson, Morghan; Aniyan, Cherene (Labour / Le Travail, 2026)
This article analyzes Wages for Housework and Wages Due Lesbians organizing in Canada through three local case studies in Vancouver, Winnipeg, and Toronto, showing how struggles over unpaid caring labour generated feminist alliances across race, class, sexuality, and immigration status. Using interviews with movement leaders and rank-and-file activists alongside private and public archival collections, it traces both solidarities and conflicts between these Marxist feminist groups, low-income mothers, immigrant women’s organizations, Indigenous women, and mainstream feminist bodies such as the National Action Committee on the Status of Women. The authors argue that Canadian Wages for Housework and Wages Due Lesbians activism was locally vibrant, transnationally connected, and has left a durable legacy in contemporary organizing around welfare rights, immigrant domestic workers, queer politics, and the recognition of women’s unpaid and underpaid care work.

Policy Analysis of Canadian Occupational Health and Safety Legislation and Regulations: Workplace Protections for Reproductive Health and Fetal Development - Jahel, Fatima; Phillips, Karen P. (New Solutions: A Journal of Environmental and Occupational Health Policy, 2026)
Canada's occupational health and safety (OHS) legislative frameworks describe the general rights and responsibilities of employers and employees to ensure safe workplaces. However, the extent to which these OHS frameworks recognize and safeguard reproductive health and fetal development remains understudied. Protections for reproductive health and fetal development were evaluated in OHS legislation, employment standards, and associated regulations across Canada's federal and 13 provincial/territorial jurisdictions by a policy analysis, supported by a sex and gender-based thematic and content analysis. OHS and reproductive health keyword frequencies were also determined. Three major themes were identified: (1) inconsistent recognition of workplace risks to reproductive health, (2) job modification, and (3) employer-mandated pregnancy leave. Our review found that workplace protections were generally limited to pregnancy, with little recognition of workplace risks to fertility, suggesting gaps in workplace protections for reproductive health and fetal development. We recommend contemporary reform of Canada's OHS legislation and regulations to support universal, comprehensive, and inclusive protections for reproductive health and fetal development for all workers, regardless of sex and pregnancy status.

After Redress: Japanese Canadian and Indigenous Struggles for Justice - Komori, Jane (Labour / Le Travail, 2026)
This article reviews the book, "After Redress: Japanese Canadian and Indigenous Struggles for Justice," edited by Kirsten Emiko McAllister and Mona Oikawa.

A Brilliant Red Thread: Revolutionary Writings from Don Hamerquist - Latham, Graham (Labour / Le Travail, 2026)
This article reviews the book, "A Brilliant Red Thread: Revolutionary Writings from Don Hamerquist ," by Don Hamerquist; edited by Luis Brennan.

200 ans de cohabitation sociale - LeBoutillier, Emma (Labour / Le Travail, 2026)
This article reviews the book, "200 ans de cohabitation sociale," by Camille Champagne-Tremblay and Martin Petitclerc.

Remapping an Ableist World: Disability and Oppression Under Capitalism - Lieffers, Caroline (Labour / Le Travail, 2026)
This article reviews the book, "Remapping an Ableist World: Disability and Oppression Under Capitalism," by Vera Chouinard.

Good Enough to Work, Good Enough to Stay: Domestic Work, Feminist Publishing, and the Archive - Lobo, Rachel (Labour / Le Travail, 2026)
The International Coalition to End Domestic Exploitation (intercede) was a Toronto-based organization that began to mobilize in 1979 in response to the growing crisis of abuse faced by domestic workers as a result of exclusionary immigration laws and the absence of workplace rights. The organization convened its activism on three main fronts: lobbying the federal government for new immigration policies that would allow domestic workers to settle in Canada permanently; petitioning for basic protections for domestic workers to be enshrined under provincial labour laws; and undertaking public advocacy that politically linked issues of women’s rights, workers’ rights, and migrant justice through transnational analysis and coalition building. Despite the unprecedented achievements made by intercede, it has largely been excluded from histories of workers’ struggle in Canada. This essay looks at the publication archive of Domestics’ Cross-Cultural News (dc-cn), a monthly newsletter published by intercede from 1984 to 2006 and housed within the online collection of the Rise Up! Feminist Digital Archive. As one of only a few periodicals produced by racialized women during this period, dc-cn is not only culturally significant but also an important historiographical tool, offering insight into how work and workers’ struggles have been racialized and gendered within a multicultural and transnational framework. This essay therefore positions dc-cn as a rich artifact that allowed domestic workers to become narrators of their own historical experience.
Keywords: domestic work; feminist print cultures; labour history; social movements; transnational feminisms

Canada’s Women’s Land Army: Wartime Labour and the Power of Visual Evidence - Lonie, Kelsey (Labour / Le Travail, 2026)
This research note examines Canada’s wartime Women’s Land Army and associated farmerette programs to highlight the value of visual sources for understanding women’s agricultural labour during the First and Second World Wars. Drawing on twenty photographs of women working in orchards, fields, and canneries alongside feminist ethnohistorical methods, it shows how images of uniforms, camp life, and physically demanding farm work both document women’s contributions to the war effort and recover experiences largely absent from conventional archives and policy records. The author argues that combining visual evidence with narrative and reflexive analysis can personalize the historical record, challenge male-centred accounts of wartime labour, and make scholarship on rural women’s work more accessible beyond academia.

Oil Money: Middle East Petrodollars and the Transformation of US Empire, 1967-1988 - Miller, Matthew (Labour / Le Travail, 2026)
This article reviews the book, "Oil Money: Middle East Petrodollars and the Transformation of US Empire, 1967-1988," by David Wight.

Claiming the City: A Global History of Workers’ Fight for Municipal Socialism - Naylor, James (Labour / Le Travail, 2026)
This article reviews the book, "Claiming the City: A Global History of Workers’ Fight for Municipal Socialism," by Shelton Stromquist.

The Surplus Value and De-Alienation of Working-Class Literatures: On the Work of Chris Pannell - Neilson, Shane (Humanities, 2026)
Though working-class literatures poorly fit within the theoretical purview of contemporary literary studies, the absence of scholarship in the Canadian context is particularly acute. Neoliberal readings thrive at the expense of labour-focused readings, with the possible result of insulating against the desired change such readings wish to bring into being. Because Chris Pannell’s poetry is so focused on work, its representations and spiritual qualities amidst a particular post-industrial location (Hamilton, Ontario), it makes for poetry well suited my goal: to create an ambidextrous reading method. In this article, I summarize the work done to date in Canadian literary studies on both labour and neoliberalism. Due to the relatively thin literature in CanLit available over the past few decades, I bring in Lukács and some American literary scholars (Jameson, Christopher and Whitson, Clarke) to round out what a working-class literature might be theorized as, and read as, in Canada while also keeping in view how critiques of neoliberalism are inadequate to the task of serving the working-class. To recalibrate Canadian literary studies, I bring forward Marx’s ideas concerning surplus value and alienation as they pertain to the production of poetry. While acknowledging the contributions of critiques of neoliberalism in Canadian literature, I critique those readings as rooted in Marx.
Keywords: Canadian literature; alienation; neoliberalism; poetics

Comrades in Art: Artists Against Fascism 1933-1943 - Niergarth, Kirk (Labour / Le Travail, 2026)
This article reviews the book, "Comrades in Art: Artists Against Fascism 1933-1943," by Andy Friend.

Democracy’s Decline: What’s Class Got to Do with It? - Pilon, Dennis (Labour / Le Travail, 2026)
This paper critiques the dominant literature on democratic backsliding, arguing that contemporary analyses overemphasize normative decline, populist leadership, and political culture while neglecting the structural role of capitalism. While influential accounts, such as Levitsky and Ziblatt’s focus on eroding norms of mutual toleration and institutional restraint, explain how democratic erosion occurs, they offer limited insight into why the postwar democratic consensus has fractured. Drawing on critiques such as Adam Tooze’s, this study contends that existing scholarship remains analytically thin in its treatment of power. In particular, it highlights the systematic absence of class analysis and the reduction of “the economy” to market fluctuations rather than a set of historically contingent, coercive social relations. Revisiting mid-20th-century critical theorists, including C. Wright Mills, Ralph Miliband, and Göran Therborn, the paper argues for a renewed engagement with the relationship between capitalism and democracy. It suggests that without integrating class dynamics and structural inequalities into analyses of democratic decline, current scholarship risks offering incomplete diagnoses and inadequate remedies for the crisis facing Western democracies.

The Changing Class Basis of Canadian and Social Democratic Futures - Polacko, Matthew; Graefe, Peter; Kiss, Simon (Perspectives, 2026)
Elements of a redistributive and working-class agenda are already in demand, but many voters and especially the working class, feel politically alienated and disaffected that their interests are not being pursued.

Caring Labour and Domestic Violence Shelter Work in the COVID-19 Pandemic - Quinlan, Andrea; Singh, Rashmee; Olenewa, Jenniffer (Social Problems, 2026)
Caring labour has long been a key part of the labour required of domestic violence shelter workers. Under the weight of public health directives during the COVID-19 pandemic, the nature and consequences of this caring labour changed. This paper examines these shifts within the broader context of the enduring invisibility of caring labour and the depoliticization of anti-violence work, both of which began long before the COVID-19 pandemic and has endured after. Drawing on 38 semi-structured interviews with shelter staff and residents working and living in domestic violence shelters in Ontario, Canada in 2022, we examine the pandemic-related shifts in shelter work and their wide-reaching consequences for workers, survivors, and anti-violence work.

A Timely Exhibit in a Gem of an Archive: Labour, Feminism, Trade, and Free Trade, Then and Now - Sangster, Joan (Labour / Le Travail, 2026)
This article analyzes a contemporary online exhibit from the Canadian Women’s Movement Archives that explores feminist perspectives on labour, trade, and free trade in Canada from the 1970s to the 1990s, situating these struggles within broader debates over capitalism, neoliberalism, and imperialism. Drawing on archival materials documenting organizing by socialist, Marxist, and labour feminists, unions, and community groups, it highlights how critiques of unpaid domestic work, precarious wage labour, and the Canada–US free trade agreement were intertwined with concerns about sovereignty, social programs, immigration, and human rights in the Global South. The article argues that the exhibit’s explicitly political curatorial stance illustrates the importance of “outsider” and community-linked archives for preserving and interpreting the histories of labour, feminism, and the Left, while tracing how earlier feminist economies prefigure later critiques of global trade bodies such as the WTO and IMF.

Labour and the NDP: Revisiting the Past, Looking to the Future - Savage, Larry (Perspectives, 2026)
The NDP’s ability to credibly advance this alternative vision depends largely on whether the labour movement is itself willing and able to engage in such political and economic education.

The Working Class and Politics in Canada - Savage, Larry (Labour / Le Travail, 2026)
This article reviews the book, "The Working Class and Politics in Canada," edited by Jacob Robbins-Kanter, Royce Koop, and Daniel Troup.

“When We Fight, We Win”: Migrant Domestic Worker Organizing and Engaged Intersectional Research in Canada - Shaw, Jennifer E.; Minh, Anita; Massie, Alicia; Bagon, Cenen; Cordero, Kassandra; Mũrage, Alice; Calamba, Rincy Dominic C.; Rosario Martinez, Noemi (International Feminist Journal of Politics, 2026)
Migrant domestic workers have formed the backbone of Canada's care economy, filling gaps in care and performing this undervalued work since the inception of the settler-colonial state. Premilla Nadasen (2023) argues that the care economy is not only subject to the sexist devaluation of women's reproductive work but is rooted in slavery and the racist extraction of work that makes all other work possible. Nadasen also points to the history of resistance, noting that care work has not only been a site of oppression but also a site of resistance. In Canada, stories of exploitation and activist-led change in the care sector have unfolded over two centuries. In the late nineteenth and early twentieth centuries, British women were brought to Canada as nannies. Fitting the image of the white nation brazenly embodied in immigration policies, these white women were provided permanent status on arrival. When the post-World War II period brought larger gaps in care, the Canadian state initiated the West Indian Domestic Scheme in 1955.... --Introduction

Racialized Agrarian Labour Regimes in Canada: Punjabi Farmworkers’ Struggles in the 1980s - Singh, Paramjit (Human Geography, 2026)
This article examines the conditions and struggles of Punjabi farmworkers in Canada during the 1980s, highlighting their resistance to exploitation within a racialized agrarian capitalist system. Focusing on the systemic challenges faced by these workers, the analysis underscores how exploitative practices perpetuated through the capitalist–contractor–corporate food regime shaped the economic and social realities of Punjabi farmworkers. The article also explores the pivotal role of the Canadian Farmworkers Union in mobilizing grassroots action, advocating for workers’ rights, and addressing systemic inequalities. By situating these efforts within broader labor movements, the study sheds light on the intersections of migration, labor, and racial capitalism in Canadian agriculture that still continue in the form of the seasonal agricultural worker program.

Tommy Douglas and the Quest for Medicare in Canada - Smith, Charles (Labour / Le Travail, 2026)
This article reviews the book, "Tommy Douglas and the Quest for Medicare in Canada," by Gregory P. Marchildon.

Poisoned Fields, Fated Lives: Destiny Politics in A Time to Rise - Soomal, Sajdeep (Labour / Le Travail, 2026)
This article examines destiny politics in Anand Patwardhan and Jim Munro’s 1981 documentary A Time to Rise (Uthan da Vela), a film that captures the political struggles of Punjabi farm workers as they organized to establish the Canadian Farmworkers Union (cfu). It argues that the film highlights how Punjabi farm workers in British Columbia could not build a life beyond the exploitative and toxic labour conditions of BC farms without first confronting powerful cultural and religious ideas about predestined life. This article demonstrates that the three main figures involved in making the film – Anand Patwardhan (the filmmaker), Pritam Kaur Hayre (the protagonist), and Sant Ram Udasi (the singer) – each sought to dismantle the hold of destiny politics over the future. First, I explain that A Time to Rise marked a first experiment with what was to become Patwardhan’s signature style of documentary filmmaking: talking groups. Through this reconfiguration of the documentary as a tool for collective dialogue and movement building, Patwardhan sought to break the enduring power of destiny within South Asian communities. Second, I discuss the film’s protagonist Pritam Kaur Hayre, who contested the politics of destiny by seeking a better life through the union rather than the Punjabi family. Lastly, I show how upending destiny politics was a central preoccupation in the anti-caste thought of Sant Ram Udasi, the Mazhabi Punjabi farm-worker-turned-activist who visited British Columbia in 1979 and wrote and performed the film’s titular song, “Uthan da Vela.”
Keywords: Anand Patwardhan; British Columbia; Punjabi feminism; South Asian diaspora; anti-caste philosophy; chemical exposures; destiny; documentary film; farm worker unions

Exceptional Exceptionalism: Does Section 107 of the Canada Labour Code Authorize the Federal Government to Terminate or Suspend the Freedom to Strike by Executive Order? - Tucker, Eric M. (Labour / Le Travail, 2026)
Recently the federal government has invoked section 107 of the Canada Labour Code to order the end of otherwise lawful strikes. The government’s claim that the section provides it with this power is in dispute. This research report, adapted from an expert witness report prepared for the law firm representing one of the unions subjected to these orders, investigates the historical understanding of the section and its precursors dating back to its earliest version, enacted in 1918. It finds that the historical understanding of the section was that its purpose was to strengthen statutory conciliation processes, not to empower the government to end otherwise lawful strikes by executive action. This government action not only continues a longer history of exceptionalism in collective bargaining but also marks a rupture by its attempt to enhance the power of the executive.
Keywords: Canada; Canada Labour Code; government interference; history; labour law; right to strike

We Always Had a Union: The New York Hotel Workers’ Union, 1912-1953 - Webb, Brandon (Labour / Le Travail, 2026)
This article reviews the book, "We Always Had a Union: The New York Hotel Workers’ Union, 1912-1953," by Shaun Richman.

A Political Economy of Canadian Broadcasting: Public Good Versus Private Profit - Webb, Jeff (Labour / Le Travail, 2026)
This article reviews the book, "A Political Economy of Canadian Broadcasting: Public Good Versus Private Profit," by David Skinner.